Effect of Sinonovacula constricta on sediment microbial numbers and easily degradable organics in shrimp-crab polyculture systems - Liu, Huiling; Chai, Xinru; Zhang, Dongxu; Xu, Wenjun; He, Jie (Frontiers in Marine Science, 2022)
To explore the influence of different densities of Sinonovacula constricta on the composition of easily degradable organic matter and related functional bacteria, four experimental ecosystems were established: three polyculture systems (PMB1, PMB2, and PMB3) of Portunus trituberculatus and Marsupenaeus japonicus with different stocking densities of S. constricta (11.6, 23.1, and 34.7×104 ind./hm2, respectively) and a polyculture system with only P. trituberculatus and M. japonicus (PM). Among the easily degradable organic components in all aquaculture systems, protein content was the highest (0.74% 0.86%), followed by carbohydrates (0.16% 0.21%) and lipids (0.06% 0.13%). In the high-density (34.7×104 ind./hm2) S. constricta mixed culture system, the contents of carbohydrates, lipids, and proteins in the sediment were significantly lower than those of the other polyculture systems. The number of cellulose-decomposing bacteria in PMB3 was 3.79×106 cfu/g, which was significantly higher than that in the other systems. The number of starch-degrading bacteria and glutin-degrading bacteria was the lowest in PMB3, 1.26×104 cfu/g, and 160.00 cfu/g, respectively. The number of lipid-degrading bacteria in PMB3 was 0.77×104 cfu/g, which was significantly lower than that in the other systems. The easily degradable organics content in sediment was significantly positively correlated with the corresponding functional bacteria. The results showed that mixed culture of S. constricta could reduce the content of easily degradable organics in the sediment of mariculture ponds and change the number of functional bacteria in the sediment and the availability of degradable organic sediments may determine the abundance of corresponding degradable bacteria.